2014
DOI: 10.2298/pif1403177n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biological insecticides NeemAzal T/S and pyrethrum FS EC and their interaction with organic products in treatments of pea aphid Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae) on Pisum sativum (L.)

Abstract: SUMMARYThe efficacy and effects of two biological insecticides, NeemAzal T/S ® and Pyrethrum FS EC, applied individually and in combination with Polyversum (a biological growth regulator and fungicide) and Biofa (an organic foliar fertilizer), in controlling Acyrthosyphon pisum population density were studied. Nurelle D (a synthetic insecticide), applied alone and in combination with Flordimex 420 (a synthetic growth regulator), was used as a standard. The products were applied once (at budding stage) or twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although Entrust provided ineffective GPA control in our trials, several studies show moderate levels of control efficacy ranging from 41% to 64% against several aphid species [ 53 , 54 ]. Field trials testing the control efficacy of pyrethrin combined with azadirachtin against PA generally showed some suppression (<30%) but not enough to provide effective control [ 55 , 56 ]. Our results on PA are consistent with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…Although Entrust provided ineffective GPA control in our trials, several studies show moderate levels of control efficacy ranging from 41% to 64% against several aphid species [ 53 , 54 ]. Field trials testing the control efficacy of pyrethrin combined with azadirachtin against PA generally showed some suppression (<30%) but not enough to provide effective control [ 55 , 56 ]. Our results on PA are consistent with these findings.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the damage value reaches up to hundreds of millions of dollars every year [2]. Synthetic chemical insecticides are mainly used in agriculture to protect crops from pest attacks, including pea aphids [4,5]. This conventional approach is relatively effective and its ability to maintain pest populations under economically acceptable levels has been widely demonstrated [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of such insecticides are their broad target spectrum , low human and mammal toxicity and a relatively low persistence in the environment , Sundaram 1996a, Morgan 2009. One severe disadvantage, however, is a varying and sometimes low efficacy of neem products in the control of rapidly developing insects such as aphids, especially in comparison to synthetic insecticides , Nikolova and Georgieva 2014, Bartelsmeier et al 2018.…”
Section: Introductionmentioning
confidence: 99%